PENANAMAN NASIONALISME KETURUNAN ARAB DALAM LEMBAGA PENDIDIKAN AL-IRSYAD AL-ISLAMIYYAH PEKALONGAN TAHUN 1918-1942 - Afriani, Risna (Puslitjakdikbud Balitbang Kemdikbud, 2018)
AbstractThe establishment of Al-Irsyad as an organization and educational institution born of Arab descent, is expected to have a role in instilling Indonesian nationalism for Arab descendants. However, there is a presumption that Al-Irsyad education does not at all instill Indonesian nationalism homeland, but Hadramaut’s nationalism. The above problems become the basis of this research, especially about how the nationalism of Arabian descent in the Institute of Education Al-Irsyad Al-Islamiyyah Pekalongan year 1918-1942. As for the purpose of this research to know; first how the education system in Al-Irsyad Al-Islamiyah Education Institution of Pekalongan in 1918-1942, second, the inculcation of nationalism into Arabic descendants by Al-Irsyad Al-Islamiyah Education Institution of Pekalongan in 1918-1942. The study employed the historical, by method the selection of the topic to study. the collection of sources (heuristic), verification or source criticism, and interpretation historiography or history writing. The results of the study were as follows; First, the education system in Al-Irsyad of Pekalongan was the modern Islamic education system that combined Islamic religion teaching and general knowledge, the Arabic language subject became a compulsory subject. Second, the inculcation of nationalism into Arabic descendant was done through the education system of Al-Irsyad of Pekalongan which had Indonesian characteristics such as the use of the Indonesian language as a medium of instruction in learning activities, the Indonesian language subject, and the admission of students from the indigenous community, which were capable of changing the orientation of Arabic descendants’ nationalism which was previously Hadramaut-like (the country of the ancestors of Arabic ethnic groups in Indonesia). Indonesian nationalism of Arab descent reinforced by the birth of the Sumpah Pemuda Arab Descendants of Indonesia in 1934. AbstrakDidirikannya Al-Irsyad sebagai organisasi dan lembaga pendidikan yang lahir dari keturunan Arab, diharapkan memiliki peran dalam menanamkan nasionalisme Indonesia untuk keturunan Arab pada masa pergerakan. Namun, ada anggapan bahwa pendidikan Al-Irsyad sama sekali tidak menanamkan nasionalisme Indonesia, melainkan nasionalisme ke-Hadramaut-an. Permasalahan tersebut menjadi dasar penelitian ini, terutama mengenai bagaimana penanaman nasionalisme Keturunan Arab dalam Lembaga Pendidikan Al-Irsyad Al-Islamiyyah Pekalongan tahun 1918- 1942. Adapun tujuan dari penelitian ini untuk mengetahui: pertama, bagaimana sistem pendidikan Lembaga Pendidikan Al-Irsyad Al-Islamiyyah Pekalongan tahun 1918-1942. Kedua, bagaimana penanaman nasionalisme keturunan Arab dalam Lembaga Pendidikan Al-Irsyad Al-Islamiyyah Pekalongan tahun 1918-1942. Penelitian ini menggunakan metode penelitian sejarah pemilihan topik, pengumpulan sumber (heuristik), kritik sumber (verifikasi), dan historiografi atau penulisan sejarah. Hasil penelitian menunjukkan: pertama, sistem pendidikan Al-Irsyad Pekalongan adalah sistem pendidikan Islam modern, dengan memadukan pengajaran agama Islam dan pengetahuan umum, mata pelajaran Bahasa Arab menjadi pelajaran wajib. Kedua, penanaman nasionalisme keturunan Arab melalui sistem pendidikan Al-Irsyad Pekalongan yang memiliki sifat ke-Indonesia-an seperti: penggunaan Bahasa Melayu sebagai bahasa pengantar kegiatan pembelajaran; adanya pelajaran Bahasa Indonesia; dan diterimanya murid dari masyarakat pribumi mampu mengubah orientasi nasionalisme keturunan Arab yang sebelumnya masih bersifat ke-Hadramaut-an. Nasionalisme Indonesia keturunan Arab diperkuat dengan lahirnya Sumpah Pemuda Keturunan Arab Indonesia pada tahun 1934.